The AI-Driven DBA: How Artificial Intelligence is Transforming SQL Server Database Administration - Siva Kumar Raju Bhupathiraju (International Journal of Intelligent Systems and Applications in Engineering, 2026)
AI or machine learning fundamentally changes how SQL Server database administration is done. The aim is smart, predictive, self-service, and self-optimizing database administration rather than manual and reactive or even standardization-based database administration. Modern enterprise database environments with high concurrency and high availability in hybrid cloud environments cannot be managed by standard database administration techniques, even if they are already automated. An important area of focus has been Smart Query Processing (IQP), which adds adaptive feedback features to the query execution engine to automatically adjust cardinality estimates, memory grants and join orders as queries execute, without DBA administrator intervention. A further advance is predictive workload analysis‚ where machine learning models trained on query execution telemetry identify performance degradation and capacity issues before they occur‚ turning the DBA role from performance firefighting to operational governance․ Automated index management closes the most labor-intensive maintenance loop in SQL Server administration with index configuration recommendation and validation based on missing index hints, workload patterns and usage scenarios in a self-correcting feedback loop. In the security domain, behavioral anomaly detection models create a baseline of behavioral patterns of users and applications, and their analysis allows insider data exfiltration and malicious privilege escalation and injection attempts to be detected when other controls may not. Together‚ these capabilities drastically alter the role of the database administrator from a customary operational role to one focused on governance‚ architecture‚ and clever orchestration of self-managing systems while delivering improvements in reliability‚ security posture‚ and operational efficiency across SQL Server environments of all sizes.